Crab Fattening in Bangladesh: A Socio-economic Perspective (Journal of Environmental Science and Natural Resources, 2015)
Thestudy was conducted to assess the socio-economic condition of the crab fatteners in the southwest part of Bangladesh.About 52% farmers have an experience of 5 to 10 yearsof indicating that involvement in mud crab fattening is the recent development and innovation in those areas.The Hindus in the coastal region found to have more interest in crab farming. On the other hand, about 27% Muslim were also found to involve in this farming.Comparativelyhigher involvements of Hindus farmers were found in Khulna region. Mostly young people found to have more involvement ranging from 26 to 35 years old which constituted more than 38% of the total interviewed population. About 40% farmers showedhigher satisfaction bycrab fattening while,fewfarmers reported some negative perception. Most of their farmingwere small scale and the farmers also accounted the higher seed cost with low profitability. However, well developedco-operation and partnershipbetween farmers, fishermen, middlemen and wholesaler can also improve this sector for sustainable development.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22056 J. Environ. Sci. & Natural Resources, 6(1): 145-152 2013